2021
DOI: 10.4178/epih.e2021053
|View full text |Cite
|
Sign up to set email alerts
|

Recent increase in pertussis incidence in Korea: an age-period-cohort analysis

Abstract: Objectives Pertussis or whooping cough, one of the most contagious diseases, is caused by the gram-negative bacterium Bordetella pertussis. Despite the high vaccination rate, South Korea recently experienced a resurgence of pertussis. This study explores the patterns and possible explanations of the resurgence of pertussis in South Korea using age-period-cohort analysis.Methods Using secondary data from the infectious disease portal of Korea Disease Prevention & Control Agency and Korea Statistical Information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, after 2014, there was a huge increase up to a rate of 2.15 per 100,000 in 2019, providing an important reminder that pertussis remains a threat in China. Similar to countries such as Canada, the United States, and Australia [ 36 ], the recurrence of pertussis has become an increasing problem in China. Previous studies indicated that the appearance of erythromycin-resistant B. pertussis and the evolution of B. pertussis might be the responsible for the increasing incidence in China [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, after 2014, there was a huge increase up to a rate of 2.15 per 100,000 in 2019, providing an important reminder that pertussis remains a threat in China. Similar to countries such as Canada, the United States, and Australia [ 36 ], the recurrence of pertussis has become an increasing problem in China. Previous studies indicated that the appearance of erythromycin-resistant B. pertussis and the evolution of B. pertussis might be the responsible for the increasing incidence in China [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current vaccines, both the traditional vaccine based on a suspension of the heat-killed and detoxified disease causative agent B. pertussis and the acellular vaccines made up of purified B. pertussis protein immunogens adjuvanted with Alum, have undoubtedly proved to be pivotal for the reduction in the morbidity and mortality associated with the disease. This reduction in the number of cases had been sustained for years; however, a few decades ago, the disease resurged, even in countries with high vaccination coverage [ 28 , 125 , 126 , 127 , 128 ]. The ability of pertussis vaccines to prevent transmission and provide long-term herd protection remains a major point of contention [ 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…The switch towards the use of aP component in many countries contributed to an increase in the acceptance of pertussis vaccinations within the population, leading to an increase in vaccination coverage [ 9 , 21 , 25 ]. However, a progressive rise in the number of cases has been observed for more than twenty years in Europe, as well as in other regions of the world [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In addition, increased incidence of pertussis has been reported in older children, adolescents, and adults [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Korea, the disease burden of pertussis is still high, with an annual incidence rate that peaked at 24.7 per 100,000 infants per 2018 data [15]. The highest pertussis detection rates are reported in infants (\ 6 months of age) and young children, followed by adolescents and adults [15,16]. During 2010-2011, 33.8% of patients with pertussis were \ 3 months old, and 29% were adolescents and adults C 15 years old [17].…”
Section: Introductionmentioning
confidence: 99%